'My anger is what has driven me to get this far...': Securing Positive Housing Pathways for Care Leavers in Australia. - Liddiard, Mark (SOAC: Causal Productions, 2011)
It has long been known that care leavers are far more likely to experience homelessness and insecure housing than other young people, although exactly why there is such a strong relationship between an experience of care and homelessness has been subject to considerable conjecture. This is the background to an AHURI-funded research study examining the housing pathways of young people who have left state care in Australia. This study interviewed 77 young care leavers and identified two broad pathways for young people from care into independent housing – a relatively unproblematic or smooth transition, compared to a much more problematic or volatile transition. Importantly, some three quarters of our respondents had experienced a problematic or volatile transition form care, involving homelessness and a range of significant housing problems. It is crucial to remember, however, that these housing pathways are not static and some young people are able to make tangible progress towards attaining and maintaining independent housing, often in the face of striking adversity. This paper focuses upon these housing pathways and specifically reflects upon what makes a difference to care leavers’ ability to successfully move on. Housing affordability is absolutely pivotal here, but is not the only influence. This paper argues that addressing substance abuse; providing appropriate professional support; developing supportive family relationships and securing employment are all instrumental in establishing successful housing pathways for care leavers.